Economic impact of cervical cancer premature mortality in Brazil 2001-2030: a human capital approach. (30th September 2020) - De, M; Cancela, Camargo; Borges, L; de Souza, Lopes; Leite Martins, L F; Correa Schilithz, A; Bezerra de Souza, D L; Hanly, P; Barchuk, A; Soerjomataram, I; Sharp, L; Pearce, A
Abstract: Background: Cervical cancer is a preventable disease, vaccination and screening for precursor lesions are effective primary prevention measures. Some developed countries aim to eradicate it in the near future. In Brazil, there is still a need for progress in cervical cancer control. Using the human capital approach, we estimate how much cervical cancer-related premature mortality indirectly impacts the economy through productivity loss. Given the diversity of sociodemographic profiles in Brazil, we estimated lost productivity due to cervical cancer by regions, providing evidence for local decision-makers. Methods: Data of all cancers deaths among working-age women (15-64 years) occurring between 2001 and 2015 were extracted from the National Mortality System, by region and age-group. Data on life expectancy, workforce participation, unemployment and wages were obtained from the Brazilian National Institute of Geographics and Statistics. NordPred package by software R was used to calculate predictions to 2030. Loss of productivity was calculated as the value of time between death and potential retirement age, adjusted for unemployment and participation rates. Results: Nationally, 76, 617 premature cervical deaths occurred between 2001 and 2015, and 90, 437 deaths are predicted for 2016-2030, corresponding to an observed cost of US2, 260, 623 (thousands) and a predicted cost of US4, 939, 561 (thousands). The impact of cervical-cancer related productivity varied by region. In the affluent South and Southeast regions, 14% and 11.5% of the loss related to cancer premature mortality will be due to cervical cancer (2016-2030) while in the North and Northeast, it will be responsible for 26.8% and 17.5% of the loss, respectively. Conclusions: If the situation in Brazil remains the same, the economic impact of cervical cancer deaths among working-age women will remain critical. It is urgent to reinforce primary prevention measures, especially in the North and Northeast regions. Key messages: The number of cervical cancer deaths among working-age women in Brazil is predicted to increase until 2030. It is urgent to reinforce cervical cancer primary prevention measures, especially in the North and Northeast regions.